Droplets and Sprays Applications for Combustion and Propulsion - Basu, Saptarshi; Agarwal, Avinash Kumar; Mukhopadhyay, Achintya; Patel, Chetankumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on droplets and sprays relevant to combustion and propulsion applications. The book includes fundamental studies on the heating, evaporation and combustion of individual droplets and basic mechanisms of spray formation. The contents also extend to the latest analytical, numerical and experimental techniques for investigating the behavior of sprays in devices like combustion engines and gas turbines. In addition, the book explores several emerging areas like interactions between sprays and flames and the dynamic characteristics of spray combustion systems on the fundamental side, as well as the development of novel fuel injectors for specific devices on the application side. Given its breadth of coverage, the book will benefit researchers and professionals alike.
Part I Multiphase Flow Fundamentals -- Introduction to Frontiers in Droplets and Spray Research for Combustion and Propulsion -- Towards Combined Deterministic And Statistical Approaches To Modeling Dispersed Multiphase Fows -- Part II Droplet Evaporation and Combustion -- Modelling of Droplet Heating and Evaporation -- Combustion of Multi-Component Fuel Droplets -- Part III Atomization Principles and Injection Strategies -- On Primary atomization in propulsive device fuel injectors - A short review -- A comprehensive model for estimation of spray characteristics -- Modeling of Flash Boiling Phenomenon in Internal and Near-nozzle Flow of Fuel Injectors -- Novel Fuel Injection Systems for High-Speed Combustors -- Experimental Investigation of Spray Characteristics of Kerosene, Ethanol and Ethanol Blended Kerosene using a Gas Turbine Hybrid Atomizer -- Two-Phase Characterization for Turbulent Dispersion of Sprays: A Review of Optical Techniques -- Part IV Turbulent Spray Combustion -- Turbulent SprayCombustion -- Modelling of Variance and Co-variance in Turbulent Flame-Droplet Interaction: A Direct Numerical Simulation Analysis -- Part V Droplet and Spray Dynamics -- Dynamics of Droplet Breakup -- Intermittency: A State that Precedes Thermoacoustic Instability.
Keywords: Fluid mechanics; Engines; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Fluid Dynamics; Engine Technology; Engineering Thermodynamics, Heat and Mass Transfer